Genetic Diversity and Population Structure of Serbian Barley (Hordeum vulgare L.) Collection during a 40-Year Long Breeding Period - Ljiljana Brbaklić; Dragana Trkulja; Sanja Mikić; Milan Mirosavljević; Vojislava Momčilović; Branislav Dudić; Lenka Procházková; Vladimir Aćin (Agronomy, 2021)
Determination of genetic diversity and population structure of breeding material is an important prerequisite for discovering novel and valuable alleles aimed at crop improvement. This study’s main objective was to characterize genetic diversity and population structure of a collection representing a 40-year long historical period of barley (Hordeum vulgare L.) breeding, using microsatellites, pedigree, and phenotypic data. The set of 90 barley genotypes was phenotyped during three growing seasons and genotyped with 338 polymorphic alleles. The indicators of genetic diversity showed differentiation changes throughout the breeding periods. The population structure discriminated the breeding material into three distinctive groups. The principal coordinate analysis grouped the genotypes according to their growth habit and row type. An analysis of phenotypic variance (ANOVA) showed that almost all investigated traits varied significantly between row types, seasons, and breeding periods. A positive effect on yield progress during the 40-year long breeding period could be partly attributed to breeding for shorter plants, which reduced lodging and thus provided higher yield stability. The breeding material revealed a considerable diversity level based on microsatellite and phenotypic data without a tendency of genetic erosion throughout the breeding history and implied dynamic changes in genetic backgrounds, providing a great gene pool suitable for further barley improvement.